Pengaruh Kombinasi Foot Massage Dan Aromaterapi Lavender Terhadap Fatique Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa - Delina, Delina; Siti Oktavianti, Dewi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Management of chronic renal failure includes hemodialysis and CAPD. Complications of hemodialysis are fatigue which can disrupt daily activities. One of the non-pharmacological therapies for fatigue is giving a combination of foot massage and lavender aromatherapy, which is effective in reducing fatigue. The aim of this study was to determine the effect of a combination of foot massage and lavender aromatherapy on fatigue in chronic kidney failure patients undergoing hemodialysis. The design of this research is quasi experimental with a pre-post test with control group design. The population of this study was 106 chronic kidney failure patients undergoing hemodialysis. The sample for this study was 50 respondents divided into 2 groups, namely 25 respondents in the intervention group and 25 respondents in the control group. The sampling technique uses consecutive sampling. The research instrument used was the fatigue severity scale questionnaire. The statistical test used independent t test with p value = 0.0001 (p<0.05), meaning that there was a significant difference in the mean fatigue levels between the intervention group and the control group in patients with chronic kidney failure undergoing hemodialysis. It is hoped that the results of this research can become a non-pharmacological therapy, namely providing a combination of foot massage and lavender aromatherapy which can reduce fatigue in patients undergoing HD